Adante begins to evaluate the expression 3 and one-third times 5 and one-fourth using the steps below. 3 and one-third times 5 and one-fourth 3 and one-third times (5 + one-fourth) (3 and one-third times 5) + (3 and one-third times one-fourth) (3 + one-third) (5) + (3 + one-third) (one-fourth) Which could be his next step?

Respuesta :

Answer:

(3)(5) + (1/3)(5) + (3)(1/4) + (1/3)(1/4)

Step-by-step explanation:

(3 1/3)(5 1/4) =

= (3 1/3)(5 + 1/4)

= (3 1/3)(5) + (3 1/3)(1/4)

= (3 + 1/3)(5) + (3 + 1/3)(1/4)

= (3)(5) + (1/3)(5) + (3)(1/4) + (1/3)(1/4)

Answer:

it is a.

Step-by-step explanation: